A coadapted community-based participatory group programme for parents/carers of children with complex neurodisability (Encompass-2): a pilot and feasibility study protocol - Kirsten Prest; Angela Harden; Kirsten Barnicot; Michelle Heys (Pilot and Feasibility Studies)
Abstract Background Parents/carers of children with complex neurodisability continue to lack appropriate family-centred care. “Encompass” is a community-based group programme that was co-adapted from “Baby Ubuntu” in Uganda. It is an example of a “decolonised healthcare innovation” as it is a low-cost solution from a low-income country for use in a resource-constrained UK National Health Service (NHS). Methods and analysis We will conduct a mixed-methods pilot feasibility study to determine the feasibility and acceptability of delivering and evaluating “Encompass” with parents/carers of children under 5 years with complex neurodisability in the UK. We aim to recruit 20 parents/carers of children from two NHS trusts in England serving urban areas where there is high social deprivation and ethnic diversity. Recruited parents/carers will attend the 10-modular, participatory group programme over a 6-month period. Groups will be facilitated by a trained allied health professional and an “expert parent” with lived experience. The primary outcomes of interest are the feasibility of delivering and evaluating the programme (recruitment, retention rates, acceptability as perceived by the parents/carers, facilitators and wider key NHS partners), intervention fidelity and participant adherence. Results will be collectively assessed against traffic light criteria. Pre-, post- and follow-up data collection questionnaires will include the Family Empowerment Scale (FES), the Power Ladder Question, the Parent Patient Activation Measure (P-PAM), Warwick-Edinburgh Mental Wellbeing Scale (WEMWBS), EuroQoL-5D-5-level (EQ-5D-5L) and parent/carer greatest needs and goals questionnaire. Post-intervention semi-structured interviews will be conducted with parents/carers, facilitators and key NHS partners. Discussion A community-based participatory group programme is a potentially affordable and sustainable way for the NHS to provide family-centred support. The programme aims to improve outcomes for parents/carers of children with complex neurodisability. Example outcomes include knowledge, skills, confidence, wellbeing and quality of life. The programme also provides opportunities for peer support and aims to empower parents/carers in navigating community health systems. Registration The protocol is registered on clinical trials.gov (ID: NCT06310681). Ethical approval Health Research Authority ref. 23/EM/0213.